Animals. Volume 2, birds : a Macmillan illustrated encyclopedia - Whitfield, Philip (New York : Macmillan Library Reference USA, 1999)
Contains articles that provide general information about over eighty families of birds, with descriptions of representative species within each family; discussing size, breeding patterns, feeding habits, adaptation and behaviors, common and scientific names, and conservation status.
Includes index.
Young Adult
Keywords: Animals -- Encyclopedias; Birds -- Encyclopedias; Animals -- Encyclopedias; Birds -- Encyclopedias